Bacteremia tuberculosis among HIV‐negative children in China. Issue 3 (5th September 2022) - Chu, Ping; Shi, Jin; Dong, Fang; Yang, Hui; Zhao, Shunying; Liu, Gang; Zheng, Huyong; Liu, Jinrong; Li, Huimin; Lu, Jie
ABSTRACT: Importance: Bacteremia tuberculosis (TB) is a severe form of extrapulmonary TB. Studies assessing bacteremia TB in children are limited, especially for HIV‐negative children. Objective: To explore the detailed clinical features of the bacteremia TB in children under 18 years of age. Methods: We reviewed the clinical records of the patients retrospectively and collected the strains isolated from their blood cultures. We used mycobacterial interspersed repetitive‐unit‐variable‐number tandem‐repeat (MIRU‐VNTR) to characterize the bacterial genotypes and alamarBlue to determine their drug susceptibility profiles. Polymerase chain reactions and DNA sequencing were used to identify drug‐resistant mutations. Results: There were 13 pediatric bacteremia TB patients, 10 of whom were diagnosed with Bacillus Calmette–Guérin (BCG) bacteremia TB. Thirteen patients aged from 0.30 to 11.58 years were enrolled, of whom 76.92% were boys. All had fevers before hospitalization, and 76.92% had respiratory symptoms. All had received BCG vaccinations, and 46.15% had adverse post‐vaccination reactions. Compared with Mycobacterium tuberculosis, BCG bacteremia was more likely to appear in younger children. Patients with BCG bacteremia had primary immunodeficiency diseases, and lower CD4, IgA, and IgE levels. Interpretation: Bacteremia TB was rapidly fatal in a large proportion of the immunodeficient children. Because classic findings may not be diagnostically specific, a high level of clinical suspicion is required, especially for patients with certain types of immunosuppression. Studies are needed to develop rapid diagnostic tests and to determine the value of empirical therapy in childhood bacteremia TB. Abstract :